1964
DOI: 10.3382/ps.0430947
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Selenium and Age upon the Metabolism of Selenium-75 by Chicks ,

Abstract: The selenium content of the ration was calculated to be 0.5 p.p.m. 4 To prevent confounding protein level and age and to eliminate the effect of protein level on selenium toxicity (Moxon and Rhian, 1943), a 20% protein grower ration was fed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1964
1964
1970
1970

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The concentration in the liver and kidney was significantly higher than in blood, pineal or cerebellum. These results are in agreement with the results of Wright and Bell (1964) with sheep and Wright and Mraz (1964) with chickens, but they differ in some detail from results reported by Jensen et al (1963), with young chicks. The latter found the highest values in blood, followed in order by the spleen, kidney and liver.…”
Section: [D = )supporting
confidence: 77%
See 1 more Smart Citation
“…The concentration in the liver and kidney was significantly higher than in blood, pineal or cerebellum. These results are in agreement with the results of Wright and Bell (1964) with sheep and Wright and Mraz (1964) with chickens, but they differ in some detail from results reported by Jensen et al (1963), with young chicks. The latter found the highest values in blood, followed in order by the spleen, kidney and liver.…”
Section: [D = )supporting
confidence: 77%
“…Implication of selenium in muscular dystrophy and exudative diathesis and fertility in chickens, as well as in a muscular myopathy (white muscle disease) of calves and lambs, is discussed in detail in Selenium in Biomedicine (Muth, 1967) and by Scott (1966), Savage (1968), Wright and Mraz (1964) and Jensen (1968). For a comprehensive review of selenium, readers are referred to Rosenfeld and Beath (1964).…”
mentioning
confidence: 98%
“…After two hours the major portion of the dose was found in the beta and gamma fractions and the activity in these fractions increased with time. Other investigators also reported a decreased retention of Se75 by feeding stable selenium, an effect not influenced by age of bird or length of time it received the seleniferous diets (171).…”
Section: Trace Elementsmentioning
confidence: 91%